The Retinal Renin-Angiotensin-Aldosterone System: Implications for Glaucoma - Kazuyuki Hirooka; Yoshiaki Kiuchi (MDPI AG, 2022)
Aldosterone is one of the main effectors of the renin-angiotensin-aldosterone system (RAAS) along with having roles in hypertension, and cardiovascular and renal diseases. Recent evidence has also shown the presence of an active local RAAS within the human eye. It has been shown that at 12 h after a retinal ischemia-reperfusion injury, there is an upregulation of the protein levels of angiotensin II type 1 receptor (AT1-R) in the retina. Furthermore, at 12 h after reperfusion, there is an increase in reactive oxygen species (ROS) production in the retina that is mediated via an NADPH oxidase pathway. This ischemia-reperfusion injury-induced increase of retinal ROS levels and NADPH oxidase expression can be prevented by the administration of an AT1-R antagonist. This suggests that one of the main retinal ischemic injury pathways is via the local RAAS. It has also been reported that progressive retinal ganglion cell loss and glaucomatous optic nerve degeneration without elevated intraocular pressure occur after administration of local or systemic aldosterone. Elucidation of glaucoma pathogenesis, especially normal-tension glaucoma (NTG) subtype by our current animal model can be used for identifying potential therapeutic targets. Based on these results, we are further evaluating NTG prevalence among primary aldosteronism patients.